Openbare toiletten in de Brusselse openbare ruimten: noodzaak of overlast? - Lien Maes; Lucas Melgaço (Brussels Studies, 2023)
For public spaces to be both accessible and hospitable, the provision of good quality public toilets is essential. This is particularly true for women as well as more specific groups, including older adults, people with health conditions or impairments, and those experiencing homelessness. Despite their importance, public toilets commonly conjure notions of dirtiness and nuisance, or of spaces used for purposes for which they were not intended, such as drug use, sexual encounters or shelter. Public toilets, therefore, reflect the complexity of shared public spaces. With a focus on Brussels, relevant authorities and organisations were interviewed, and on-site observations were carried out to explore the importance of public toilets for public spaces. The article is attentive to the nuisances linked to public toilets, and the difficulties in generating effective responses to their so-called misuse.